Investigating the Effects of Crises and Bilateral Agreements on Moldova's Economic Integration into the European Union Using the Trade Intensity Index Method - Selamzade, Fuad; Baghirov, Alig; Ahmedov, Ahmed; Rustamov, Tural (My University, 2025)
The main objective of this research is to evaluate the bilateral trade and economic relations between Moldova and the European Union (EU) from 2003 to 2023 using the trade intensity index analysis method. It also examines how external events such as the 2008 Global Financial Crisis and the COVID-19 pandemic, as well as bilateral agreements, have impacted Moldova's integration process into the European Union. According to the analysis results, the trade intensity score between the European Union and Moldova is above the world average, with the European Union having nearly twice the trade intensity score compared to Moldova. Positive agreements, such as the European Union Eastern Partnership Program initiated in 2009, have been found to have beneficial effects on Moldova's economic integration with the European Union. On the other hand, external events like the 2008 Global Financial Crisis and the COVID-19 pandemic have been determined to have negative impacts on Moldova's integration into the European Union and its bilateral trade and economic relations. The study indicates that while the EU Eastern Partnership Agreement has positively influenced Moldova's economic integration, the process remains vulnerable to financial crises and global disruptions, underscoring the need for resilient trade policies and strategies to revitalize economic cooperation amid declining trade volumes.
Keywords: İktisat; Uluslararası İlişkiler